(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2019)
The concentration of Cd in the liver and muscle of Guanchiche (H. microlepis) and Dica (Pseudocurimata bolengeri) was determined. The concentration of the metal in the muscle tissue of the species is less than the limit of quantification of the method (<0.014 mg / Kg). The highest concentration of Cd in the liver will be identified in the P. boulengeri species (0.63 ± 0.188 mg / kg) and the lower concentration in H. microlepis (0.003 ± 0.036 mg / kg), there are significant differences in the concentration of Cd of the livers of both species (F = 33.74; p = 0.000). One-way ANOVA and a posterior test of Tukey (p <0.05). The concentration of Cd in the liver is above the maximum permissible limit (0.05 mg / kg) established by the European Union. The correlation between weight and height was directly proportional to each other (r = 0.963; p = 0.000) the concentration of Cd in the liver was inversely proportional to height and weight and sexual maturity was directly direct proportional to the concentration of Cd (r = 0.880; p = 0.000).